2007
DOI: 10.3892/or.17.4.769
|View full text |Cite
|
Sign up to set email alerts
|

Bax gene therapy for human osteosarcoma using cationic liposomes in vivo

Abstract: Abstract. The purpose of this study was to evaluate the anti-tumor effect of human osteosarcoma (HOSM-1) tumor xenografts in nude mice via transfer of the Bax gene using cationic liposomes. The HOSM-1 tumors transplanted into nude mice grew to 5-6 mm in diameter. Following growth of the tumor to this size, liposomes with the Bax plasmid were applied locally to the peripheral tumor (day 0) and were applied 3 times per week for 2 weeks (6 times in total). The tumor growth inhibitory effect was evaluated by measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Apoptosis-related genes such as p53, p73, Bax and PDCD5 [1][2][3][4] have been used in gene therapy to directly induce apoptosis or by synergistically enhancing the effects of chemotherapy in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis-related genes such as p53, p73, Bax and PDCD5 [1][2][3][4] have been used in gene therapy to directly induce apoptosis or by synergistically enhancing the effects of chemotherapy in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in understanding the molecular pathogenesis of cancer and the rapid development of recombinant DNA technology have made cancer gene therapy feasible in the clinical setting. Apoptosis-related genes such as p53, p73, and Bax [4][5][6] have been used in gene therapy to directly induce apoptosis or by synergistically enhancing the effects of chemotherapy in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…2,15,18,21,22,[33][34][35] Bax apoptotic activity is regulated by the translocation of bax to the mitochondria, where it induces mitochondrial membrane permeabilization. 24,25 It is believed that conformational changes in bax under apoptotic stimuli initiate bax translocation to the mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…14 Bax, a member of the bcl2 family of genes, has been extensively studied as a candidate for suicide gene therapy. [15][16][17][18][19] Although regulation of bax by hTERT promoter in an adenovirus vector has been shown to provide tumor-specific activity without hepatotoxicity, 2,20 the use of bax as a suicide gene in nonviral plasmid-based vectors has only been successful with cytomegalovirus (CMV) promoter 21,22 and not with TSPs. 23 Recent evidence has shown that bax apoptotic activity is regulated by translocation of cytoplasmic bax to the mitochondria under apoptotic stimuli.…”
Section: Introductionmentioning
confidence: 99%